The new encyclopedia británica in 30 volumes, macropedia Volume 7 / William Benton - Benton, William (1977)
The early law of evidence, a comparative survey of the principles of legal evidence, the classic means of proof, adaptations of the basic systems, natural selection, variation, the synthetic theory of evolution, natural selection in action, the rate of evolution, the origin of life, sex plants, and, animals, viruses, multicellular organization, humanization, psychosocial evolution, sociology before Darwin.